Heavy metals uptake by rye grass (Lolium multiflorum) in two soils of the Rio Grande do Sul State - Pombo, Leda Cabral Amaral (Pesquisa Agropecuaria Brasileira, 1995)
In order to evaluate the uptake of heavy metais by plants, an experiment in pots, in open air, was conducted with two red-yellow podzolic soils of the Rio Grande do Sul state, Brazil, where rye grass was grown. The heavy metals Ni, Pb, Cd, Zn and Cu, in two levels, were added to the soils, in the residue derived from the SITEL, the integrated wastewater treatment of Pólo Petroquímico do Sul (South Petrochemical Complex) applied in doses of 0, 5.0 and 8.5 g kg-1. The heavy metals in the residue were distributed in forms of different availabilities. The lack of toxicity symptoms and the high tolerance indeces showed that the heavy metals, in the study conditions, did not damage the rye grass growth. The chelating agents EDTA and DTPA were not efficient to evaluate the available Pb and Ni, and the CaCl2 was the more efficient extraction reagent to evaluate the available Cd to the plants.
Keywords: podzolic soil; extractants